Impunidade (?) nos crimes de colarinho branco : a (in)eficiência da reação punitiva no delito de evasão de divisas no âmbito do TRF4 - Soto, Rafael Eduardo de Andrade (2013)
This study, performed along the research line of Criminology and Social Control, from Pontifícia Universidade Católica do Rio Grande do Sul`s Post Graduation Program in Criminal Science, examines the effectiveness of secundary criminalization by punitive reaction to crimes of tax evasion in the last five years. The research was conducted under the Federal Regional Court of the 4th Region, beneath the joint resolutions of appeals, since they are the final analysis from the set of evidentiary proceedings. Thus, we sought to determine whether the characteristics of the white-collar criminal collaborate to impunity and, in cases of conviction, which is its effectiveness, according to the punitive models. The paper explains how the selectivity is performed to primary criminalization and recalls the punitive models since the idea of punishment to the notion of abolitionism as an alternative mean. At the end, the decisions from 2008 to 2012 were analyzed according to the central hypothesis of impunity.